Age-specific anti-Müllerian hormone and electrocardiographic silent coronary artery disease. (3rd July 2016) - Ramezani Tehrani, F.; Montazeri, S. A.; Khalili, D.; Cheraghi, L.; Broekmans, F. J.; Momenan, A. A.; de Kat, A. C.; Azizi, F.
Abstract: Objective: To explore the relationship between age-specific anti-Müllerian hormone level, as a predictor of ovarian reserve status, and electrocardiographic silent coronary artery disease in a population-based, prospective cohort, the Tehran Lipid and Glucose Study. Methods: For the present study, 1015 reproductive-aged participants in the Tehran Lipid and Glucose Study met our eligibility criteria. According to the Whitehall criteria, silent coronary artery disease was defined as an electrocardiogram showing possible or probable coronary heart disease using Minnesota codes. By excluding those with a history of coronary heart disease and silent coronary artery disease at the initiation of the study ( n = 49), there were 108 events of silent coronary artery disease at electrocardiograms among 752 women followed for 9.5 ± 0.9 years (missing data: n = 214); the association between this outcome with age-specific anti-Müllerian hormone levels was explored after adjustment for confounding variables using logistic regression analysis. Cardiovascular disease risk scores were assessed for all participants using the guidelines of the American College of Cardiology and the American Heart Association. Results: There were 108 events of silent coronary artery disease over the 10-year follow-up. Logistic regression analysis, considering age-specific anti-Müllerian hormone and atherosclerotic cardiovascular disease risk score as independent variables, revealed an odds ratio of 1.146 (95% confidence interval 1.008–1.303) for cardiovascular disease risk score ( p = 0.038) and odds ratio of 1.002 (95% confidence interval 0.996–1.009) for age-specific anti-Müllerian hormone ( p = 0.526). Conclusion: No association has been found between age-specific anti-Müllerian hormone levels and events of silent coronary artery disease in a 10-year follow-up of reproductive-aged women.